Hierarchy and scope of planning in subject–verb agreement production - Gillespie, Maureen; Pearlmutter, Neal J. (Cognition, 2011)
Two subject–verb agreement error elicitation studies tested the hierarchical feature-passing account of agreement computation in production and three timing-based alternatives: linear distance to the head noun, semantic integration, and a combined effect of both (a scope of planning account). In Experiment 1, participants completed subject noun phrase (NP) stimuli consisting of a head NP followed by two prepositional phrase (PP) modifiers, where the first PP modified the first NP, and the second PP modified one of the two preceding NPs. Semantic integration between the head noun and the local noun within each PP was held constant across structures. The mismatch error pattern showed an effect of linear distance to the head noun and no influence of hierarchical distance. In Experiment 2, participants completed NP PP PP stimuli in which both PPs modified the head noun, and both the order of the two PPs and the local nouns’ degree of semantic integration with the head noun were varied. The pattern of mismatch errors reflected a combination of semantic integration and linear distance to the head noun. These studies indicate that agreement processes are strongly constrained by grammatical-level scope of planning, with local nouns planned closer to the head having a greater chance of interfering with agreement computation.